Rancang Bangun Website E-Commerce Sebagai Media Promosi dan Peningkatan Penjualan pada Toko Sevent Sport - Aziz Hidayatulloh, Muhammad; Dharmawan, Alexander; Arizonia Ismail, Harries (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The development of information technology and the internet has brought significant changes to the business world, including the trade sector. The use of e-commerce websites today is not only a means of buying and selling but also serves as an effective promotional tool to expand market reach. Sevent Sport, a sports equipment provider, requires a system capable of supporting digital promotional and sales activities to compete with similar stores and meet the needs of customers who increasingly prioritize ease and speed of transactions. This research aims to design and build an e-commerce website that can be used as a promotional tool and increase sales at Sevent Sport. The methodology used is the Waterfall system development model, which consists of the stages of needs analysis, design, implementation, testing, and maintenance. The needs analysis was conducted to identify the problems encountered and the required features, such as a product catalog, shopping cart, ordering system, payment integration, product management, discount promotions, and transaction reports. The system design was created using UML diagrams and then implemented using the PHP programming language, a MySQL database, and a web-based supporting framework. The research results show that the e-commerce website is able to display product information in a structured manner, facilitate ordering and payment processes, and simplify the store owner's management of promotions and sales reports. Based on the results of the system testing conducted using the black box testing method, all key features functioned according to user needs. With this e-commerce website, Toko Sevent Sport can improve promotional effectiveness, expand its marketing reach, and support sales growth in the digital era.